Evaluation of Iron Ore Deposits in Elayiram Pannai, Sattur Taluk, Virudhunagar District and Tamilnadu using 2D Electrical Resistivity Imaging - Ravindran A Anthony (Journal of Applied Sciences and Environmental Management)
2D Electrical Resistivity Imaging (ERI) investigation is suitable method to determine the geotechnical problems and it is used to identify the iron ore deposits. 2D Electrical Resistivity Imaging with Wenner array was conducted within the iron ore deposits area in Elayiram Pannai, Virudhunagar District, Tamilnadu.The geology of the were developed into the picture image of pseudosection by using RES2DINVsoftware. The banded iron ore deposits are highly conductive and can be easily distinguish from pseudosection image contrast of the rocks in the studied area.